Exosomes in head and neck cancer: Roles, mechanisms and applications. (1st December 2020) - Cao, Jun; Zhang, Mengdi; Xie, Feng; Lou, Jianlin; Zhou, Xiaoxue; Zhang, Long; Fang, Meiyu; Zhou, Fangfang
Abstract: Exosomes are extracellular vesicles with a diameter of 30–100 nm that exist stably in various body fluids, including the blood, cerebrospinal fluid, urine, saliva, and serous cavity effusion. Compared with other vesicles, exosomes have a unique double-layer saclike structure and an endosomal origin. Depending on the physiological state of donor cells, there is heterogeneity in the bioactive substances present in exosomes, including proteins, RNA, DNA, lipids, and metabolites, providing a rich source of potential biomarkers for disease diagnosis. In head and neck cancer (HNC), exosomes have applications in disease diagnosis and prognosis based on liquid biopsy. Nonetheless, the functions and mechanisms of exosomes in HNC still remain unclear. Recent studies have elucidated the substances and signals transmitted between cancer cells using exosomes and have discussed tumor occurrence, development, metastasis, immune regulation, and drug resistance regulated by exosomes in HNC. In this review, we discuss these recent findings and highlight the significant role of exosomes in HNC, with a focus on the mechanism of tumor progression and the potential clinical value of exosomes as biomarkers and therapeutic targets.